The Dynamics of Power Relations and Injunctive Norms on Child Participation in Development Planning - Deden Ramadani; Johanna Debora Imelda (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2023)
DKI Jakarta is one of the provinces with many young people. Around 2.9 million people, or 29 percent of the total population in DKI Jakarta province, are children. Unfortunately, the involvement of children in development planning in DKI Jakarta is still challenging. This research uses a qualitative approach with in-depth interviews and FGD techniques with children who are members of children's forums, child beneficiaries, children's forum facilitators, and government officials. This study examines children's participation in the development planning process in three areas in DKI Jakarta through Musyawarah Perencanaan Pembangunan/Musrenbang (Regional Development Planning Consultation Forum). Furthermore, this research is intended to reveal the obstacles found in involving children in development planning. The study results indicate a dynamic of power relations between children and adults, making children unable to voice their opinions for development. In addition, injunctive norms make children's participation feel artificial and procedural. A more inclusive model of children's participation in development is needed for children in order to accelerate the achievement of the SDGs in the province.